THE DEVELOPMENT OF THE HANAFI-MATURIDI TAFSIR SCHOOL IN TRANSOXIANA DURING THE 11TH-12TH CENTURIES - Ikhtiyor Abdurakhmonov (Bright Mind Publishing, 2025)
The development of the Hanafi-Maturidi school of tafsir in Mavarounnahr in the XI-XII centuries was closely related to social and political changes. During this period, the Karakhanids, Seljuks, and other dynasties ruled, and under their influence, significant development was observed in scientific and religious fields. Various works on fiqh, kalam, and tafsir based on the Hanafi jurisprudence and Maturidi creed were written in Mavarounnahr. The development of the tafsir school during this period was mainly characterized by the focus on explaining and reinforcing theological issues based on Qur’anic verses. The commentators paid great attention to the use of ijtihad and rational analysis, along with narrations, in interpreting the Qur’anic verses. They relied on Imam Maturidi’s work “Ta’welat al-Qur’an” in their attempts to correctly interpret the meanings of the verses. Scholars like Abu Mu’in al-Nasafi and Alauddin Samarkandi made a significant contribution to the development of Qur’anic interpretation by relying on Imam Maturidi’s methodology. Another important aspect of this period’s tafsir school is that the commentators placed a great emphasis on rational analysis and ijtihad, while continuing to use narrations in their works.
Keywords: Hanafi madhhab, Maturidi teachings, Karakhanids, tafsir, Abu Mu’in al-Nasafi, Seljuks, Samarkand, aqeedah, Qur’anic interpretation.